2003
DOI: 10.1163/156854003773123401
|View full text |Cite
|
Sign up to set email alerts
|

Methyl farnesoate stimulates gonad development in Macrobrachium malcolmsonii (H. Milne Edwards) (Decapoda, Palaemonidae)

Abstract: The in uence of methyl farnesoate in the regulation of gonad development in the prawn, Macrobrachium malcolmsonii was investigated. Injection of methyl farnesoate into female and male prawns signi cantly increased mean oocyte diameter and testicular follicle diameter as well as mean ovarian indices and testicular indices, respectively. These results provide strong evidence that methyl farnesoate is involved in the control of reproduction in prawns. RÉSUMÉL'in uence du methyl-farnesoate dans la régulation du dé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…This observation correlates with the high TIs of red-phase animals, consistent with the idea that MF stimulates testicular growth either directly or indirectly in crustaceans (Kalavathy et al, 1999;Nagaraju et al, 2003;Nagaraju et al, 2006;Reddy et al, 2004). These observations are similar to previous studies in the spider crab (Libinia emarginata), which demonstrated a correlation between the reproductive status of males and MF synthesis by the mandibular organ (MO) and hemolymph levels of MF (Sagi et al, 1993;Sagi et al, 1994).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This observation correlates with the high TIs of red-phase animals, consistent with the idea that MF stimulates testicular growth either directly or indirectly in crustaceans (Kalavathy et al, 1999;Nagaraju et al, 2003;Nagaraju et al, 2006;Reddy et al, 2004). These observations are similar to previous studies in the spider crab (Libinia emarginata), which demonstrated a correlation between the reproductive status of males and MF synthesis by the mandibular organ (MO) and hemolymph levels of MF (Sagi et al, 1993;Sagi et al, 1994).…”
Section: Discussionsupporting
confidence: 90%
“…Likewise, MF synthesis rates by spider crab MO incubated in vitro were correlated with reproductive behavior (Sagi et al, 1993;Sagi et al, 1994). In addition, MF treatment has been shown to increase testicular growth in a number of crustacean species, including the freshwater field crab O. senex senex (Kalavathy et al, 1999;Reddy et al, 2004), and the freshwater prawn Macrobrachium malcholamsonii (Nagaraju et al, 2003). Our observations confirm these previous studies and demonstrate that MF treatment can stimulate testicular growth in green-phase animals.…”
Section: T-test) (B)supporting
confidence: 87%
“…No mortality was observed in MF injected group and observed all of them are in late vitellogenic stage (III) with significant increase (p<0.0001) in ovarian index (508.84%), oocyte diameter (1004.16%) and ovarian vitellogenin levels (137.57%) ( Table 1). MF is known to be involved in the regulation of reproduction in various crustaceans [18,25,28,[33][34][35][36][37]. Similar to ovarian index, oocyte diameter and ovarian vitellogenin levels, observed significant increase (p<0.0001) in the ovarian total lipid and protein in both ESX and MF injected prawns ( In MF injected animals, the lipid and protein levels were significantly increased when compared with control and eyestalk ablated animals.…”
Section: Resultsmentioning
confidence: 84%
“…In specific MF is a positive regulator for reproduction and is negatively controlled by mandibular organ inhibiting hormone (MOIH) [2,[16][17][18][19] which suppressed the synthesis and release of MF from MO. An evidence of MF on regulation of reproduction has been reported in the crab Oziothelphusa senex senex [17,19], the crayfish Procambarus clarkii [20], the prawn Machrobrachium malcamsonii [18] and the shrimp Penaeus vannameii [21]. The action of MF on reproduction in crustaceans is not yet established.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation